Gender research fellowship programme inception workshop, 15-19 August 2013, Kuching, Malaysia: workshop report - Elias, Marlène; Choo Kwang Yan; Fernández, M. (2014)
This report captures the learning and interactions that occurred during the inception workshop of the Gender Research Fellowship Programme that Bioversity coordinated in 2013-2014 as part of the CGIAR Research Programme on Forests, Trees and Agroforestry. Biophysical and social scientists came together to develop research plans for individual and comparative participatory research on gender and forest genetic resources. Participants practiced using participatory methods and spent a day in the field acquiring first-hand experience using these methods in Sarawak, Malaysia. The report can serve as a guide for training in gender-responsive participatory methods that generate quality research results and promote social learning, gender equity and the conservation of forest genetic resources.